2016
DOI: 10.3390/ijms17091489
|View full text |Cite
|
Sign up to set email alerts
|

Escaping Antiangiogenic Therapy: Strategies Employed by Cancer Cells

Abstract: Tumor angiogenesis is widely recognized as one of the “hallmarks of cancer”. Consequently, during the last decades the development and testing of commercial angiogenic inhibitors has been a central focus for both basic and clinical cancer research. While antiangiogenic drugs are now incorporated into standard clinical practice, as with all cancer therapies, tumors can eventually become resistant by employing a variety of strategies to receive nutrients and oxygen in the event of therapeutic assault. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 141 publications
(163 reference statements)
0
61
0
3
Order By: Relevance
“…Previously, reported results showed that the VM incidence in gastric carcinomas, cutaneous melanoma, esophageal stromal cancer, colorectal cancer and osteosarcoma were 28.5%, 34%, 33.3%, 19.2% and 22.7%, respectively . Intriguingly, the presence of VM is less than 50% in almost all cancer types examined to date; researchers suspect that VM may only exist in aggressive malignant sub‐phenotypes of cancers . This may explain why the occurrence of VM usually indicates a poor prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, reported results showed that the VM incidence in gastric carcinomas, cutaneous melanoma, esophageal stromal cancer, colorectal cancer and osteosarcoma were 28.5%, 34%, 33.3%, 19.2% and 22.7%, respectively . Intriguingly, the presence of VM is less than 50% in almost all cancer types examined to date; researchers suspect that VM may only exist in aggressive malignant sub‐phenotypes of cancers . This may explain why the occurrence of VM usually indicates a poor prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…This process is called vascular mimicry (VM) and was introduced in 1999 by Maniotis et al [71,72]. In this process, the tumor cells gain unusual endothelial-linked properties that make them able to form tubular structures that are supported by secreted matrix proteins such as collagen IV and VI, heparan sulfate proteoglycan (HSP) and laminin [73]. Several studies have revealed that VM is associated with aggressive breast and lung cancer types [71,74,75].…”
Section: Vascular Mimicrymentioning
confidence: 99%
“…The generation of tumor vasculature in the lungs, which are highly vascularized tissues, may occur through an alternative mechanism to angiogenesis called vessel or vascular co-option. In this angiogenesis-independent mechanism, tumor cells take over existing vascular beds from adjacent normal tissues, which means that there is no need to promote the formation of new blood vessels [73]. The co-option process in tumors occurs mainly when the tumor cells invade and grow predominantly in the perivascular environment of adjacent tissues.…”
Section: Vascular Co-optionmentioning
confidence: 99%
“…We have shown that patients with DHGP who received chemo plus Bev prior to resection had a significantly better pathologic response and OS than patients with RHGP [5]. Tumors can progress by hijacking pre-existing vessels using a co-option mechanism, which facilitates the migration of the tumor cells along the vessels of the host organ and the induction of angiogenesis through the stimulation of Ang1, Ang2 and Vascular Endothelial Growth Factor (VEGF) [8,9]. The co-opted vessels are usually supported by pericytes for stabilization, which is accompanied by the inhibition of endothelial cell (EC) proliferation and AI resistance [9,10].…”
mentioning
confidence: 99%
“…Tumors can progress by hijacking pre-existing vessels using a co-option mechanism, which facilitates the migration of the tumor cells along the vessels of the host organ and the induction of angiogenesis through the stimulation of Ang1, Ang2 and Vascular Endothelial Growth Factor (VEGF) [8,9]. The co-opted vessels are usually supported by pericytes for stabilization, which is accompanied by the inhibition of endothelial cell (EC) proliferation and AI resistance [9,10]. Ang1 and Ang2 are vascular growth factor genes that have been identified as ligands for the receptor tyrosine kinase, Tie2 [11].…”
mentioning
confidence: 99%